Explicit and implicit theories of change when designing and implementing preventive ergonomics interventions - a systematic literature review - Katarina Wijk; Svend Erik Mathiassen (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVE: In contrast to several previous papers dealing with the structure and effects of ergonomics interventions, this systematic literature review focuses on the theories concerning change processes upon which these interventions - implicitly or explicitly - have been based. METHODS: In a systematic search of 13 literature databases, 30 peer-reviewed intervention studies published between 2000-2007 were identified that provided sufficient information for the change process theory to be identified. RESULTS: Thirteen studies referred to an explicit theory of change, the most common being participatory theory, while in 17 studies, the change theory could only be discerned indirectly from the described intervention strategy. Twenty-five studies explained the reason for choosing their strategy, with a clear reference to theory or previous research, whereas five provided only a weak background. Four categories of intervention strategies for change were identified: (i) changes targeting the individual, (ii) changes focusing on the work environment, (iii) changes relying on interactions between people, and (iv) structural and organizational changes. CONCLUSIONS: A strikingly small proportion of ergonomics intervention studies have explained the theory behind the expected change process. A better awareness of the assumptions about change processes embedded in intervention strategies - whether implicit or explicit - may help in identifying and examining those ideas and processes that promote or restrict successful implementation. Such knowledge, in turn, can contribute to the development of interventions that are thoughtfully designed and effectively implemented.